Resposta das algas perifíticas da planície de inundação do alto rio Paraná às alterações de temperatura e ao enriquecimento artificial de nutrientes. - Murakami, Eliza Akane (2008)
This is the first experimental study of the manipulation of temperature and nutrients in periphytic algae communities of the Rio Paraná floodplain, and constitutes a part of the LTER (Long Term Ecological Research)/CNPq project, site 6. The study set out to evaluate via a mesocosm experiment, the influence of the decrease in temperature and the addition of the nutrients phosphorus (P) and nitrogen (N) on the structure of periphytic algae communities in terms of specific composition, richness, and abundance. It is comprised of three chapters: Chapter 1, Effect of temperature and nutrient concentration on the specific composition and richness of periphytic algae: a mesocosm experiment; Chapter 2, Response of the periphytic diatoms (Bacillariophyceae) to the alteration of temperature and artificial nutrient enrichment; and Chapter 3, Periphytic algae response to temperature changes and artificial nutrient enrichment. Diatoms were considered separately from the other classes of algae due to their dominance in the floodplain periphyton. The experiment consisted of 5 treatments: control group (C), added nutrients (P+, N+, NP+) at 25ºC, and at 15ºC without added nutrients. Glass slides were used for the periphytic algae colonization, and the samples were taken on the 15th and 31st days following colonization. Principal Components Analysis showed 63.32% of the total variability in the abiotic data on the first two axes, and the different treatments were distinguishable. In this study, a total of 285 periphytic algae taxa were recorded. The classes which most contributed to the richness where, in order: Zygnemaphyceae, Bacillariophyceae, Chlorophyceae and Cyanophyceae. In terms of abundance, the Bacillariophyceae dominated, with over 84% of the total overall periphytic algae density. The periphytic algae responded sensitively to decreases in temperature and increases in nutrient concentrations. Canonical Correspondence Analysis (CCA) showed a clear difference between the control, the cool treatment group, and the added nutrient group. The richness and, in general, the overall density, were greater in the cool treatment group. The specific composition of these treatments differed. The relative densities of some Bacillariophyceae genera were lower in the cool treatment than in the control, and others higher, principally Zygnemaphyceae. Periphytic algae responded sensitively to artificial nutrient enrichment. Species richness was favored in the groups with added nutrients, principally those with N+, followed by NP+ and P+. However, the total densities of algae were in general lower with the addition of nutrients compared with the control group. The algae responded differently to the addition of nutrients, principally P. Phosphorus may be considered a forcing agent of periphytic algae density, as can be observed by the rapid response after the addition of artificial nutrients. The addition of nutrients altered the abundance of periphytic algae classes, with the substitution of Cyanophyceae by other groups. In the specific case of diatoms, the total density was lowest in the treatments with added nutrients than in the control group, possibly due principally to the response of the A. minutissimum complex, which was dominant, and presented greater density in the control group and cool treatment. In general, relative densities were greatest in treatments with added nitrogen (N+ and NP+), except for the Achnanthidium and Cymbella genera. This study shows that with decrease in temperature and the addition of nutrients, clear changes occur in composition and abundance. It is important to remember, however, that the response of periphytic algae depends greatly on the species present in the environment. Considering the importance of periphytic algae in ecosystem productivity and the retention of nutrients in reservoirs, principally phosphorus, be aware of possible future alterations in the system's food chain.